Pengembangan Lembar Kerja Peserta Didik (LKPD) Menggunakan Model ADDIE - Wulandari, Shintia; Indra Meifiani, Nely; Sugiyono (Scholarly Journal of Elementary School, 2025)
Abstract: This research aims to describe and evaluate the feasibility of Student Worksheets (LKPD) unit material and the area of flat shapes, using the ADDIE model for 4th-grade elementary school students. This study falls the category of Research and Development (R&D). The research subjects were 4th-grade students from SDN 1 Purwoasri, with validity trials conducted on 4th-grade students at SDN 2 Purwoasri, each school having 15 students. The research findings indicate: 1) The validation by material experts resulted in an average percentage of 85.5%, concluding that the LKPD can be used without any revisions; 2) The validation by media experts yielded an average percentage of 94%, also concluding that the LKPD is suitable for use without revisions; 3) The results from trial runs and response questionnaires showed an average percentage of 91%, indicating that the LKPD is appropriate as teaching material for elementary school mathematics. Keywords: Development, LKPD, Mathematics, ADDIE